Impact of Electrical Pulse Pattern on Red Blood Cell Membranous Electroporation - Ye. K. Kozlova; V. V. Moroz; M. S. Bogushevich; P. Yu. Alekseyeva; A. M. Chernysh (Общая реаниматология)
The impact of the pattern of a pulse electrical field generated by a defibrillator discharge on the efficiency of membranous electroporation was studied in a model experiment on human erythrocytic suspension. The initial temperature and time parameters of the model were substantiated. The rate of cellular hemolysis under the action of two impulses was shown to be increased by 1.2—3.5 times as compared with that under the action of one impulse. Electroporation was more effective and its threshold was lower under the action of two heterodirectional pulses as compared with that under the action of two unidirectional ones. These dependencies are statistical.